THE INFLUENCE OF VARIOUS PLANTING MEDIA COMPOSITIONS AND CONCENTRATIONS OF GROWTH REGULATORY SUBSTANCES ON THE YIELD OF GREAT RED CHILLI - Susanto, Agus Aji; Saputro, Avisema Sigit (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
Large red chilies (Capsicum annuum L.) have high economic value in the Indonesian market. The large market demand for horticultural products provides high opportunities for farmers to increase their production, including red chilies. Efforts to get high red chili yields by using good planting media and the application of organic ZPT. This research aims to examine the composition of growing media and PGR on the generative phase of red chilies. This research was carried out from 15 May 2023 to 21 August 2023. The design used in the research was a Completely Randomized Design (CRD) which consisted of 2 treatment factors which were repeated 3 times and then 12 treatment combinations were obtained. The first factor is the composition of the growing media (M), which consists of 3 levels, namely; composition 1 : 1 : 1 (M1), composition 2 : 1 : 2 (M2), and composition 1 : 2 : 1 (M3). The second factor is the concentration of organic PGR (Z), which consists of 4 levels, namely; concentration of 0 ml/l (M0), concentration of 5 ml/l (M1), concentration of 10 ml/l (M2), and concentration of 20 ml/l (M3). The parameters observed were the appearance of the first flower, number of fruit, fruit length, fruit diameter, and fruit weight on large red chilies. Analysis of variance was carried out to analyze the data and then subjected to the Least Significant Difference (LSD) test with a level of 5%. The research results showed that the two treatment factors had no influence or were not significantly different on all observed parameters. There was no interaction between the composition of the growth media and the concentration of organic PGRs for all observation parameters.